Exploring passenger rail markets using new station catchment size and shape metrics. Issue 2 (3rd July 2018) - Lin, Ting (Grace); Xia, Jianhong (Cecilia); Ryan, Mark; Robinson, Todd; Currie, Graham; McCarney, Gary; Butorac, Donna
ABSTRACT: This paper presents a novel spatial market segmentation method to determine key user groups of a train station (such as gender, age and access mode), based on the size and shape of the station catchment area of each group. Two new indices – area ratio and composite ratio – are developed to quantify the importance of user groups for a train station. This method is applied to identify key user groups at seven train stations in Perth, Western Australia. The study offers a new way to explore the travel behaviour of train users and provides insights for rail transport planning and marketing.